Resting egg banks can facilitate recovery of zooplankton communities after short exposure to glyphosate - Portinho, Jorge L. [UNESP]; Oliveira, Henrique Nunes [UNESP]; Branco, Ciro C. Z. [UNESP] (My University, 2021)
We assessed the short-term viability and recovery of zooplankton communities after exposure to glyphosate (active ingredient—a.i.). We conducted a hatching experiment in two steps: Step 1—natural lake sediments containing resting egg banks were placed into individual trays and exposed to a solution medium of glyphosate at three different treatments (LD = Values below the detection limits, LD < 0.05, 0.44, and 0.89 mg a.i./L) for 14 days; and Step 2—we replaced the exposure solution of glyphosate with distilled freshwater, keeping them all trays under freshwater conditions for another 14 day. The results from Step 1 showed significant effects of glyphosate on the emergence patterns of resting eggs, with a reduction in hatching of rotifers, mainly at concentrations of 0.44 and 0.89 mg a.i./L. On the other hand, the results from Step 2 showed an increase in the emergence of viable eggs for rotifers after restoration of freshwater conditions in all treatments; there was no effect for total zooplankton and microcrustaceans. These findings suggest that (i) glyphosate may, effectively, impair zooplankton hatching from resting egg banks; (ii) the magnitude of the negative effects depends on the the zooplanktonic group considered; and (iii) the restoration of freshwater conditions may, in some way, allow the recovery of the zooplankton community from viable egg banks. Our results can be useful in predicting the influence of glyphosate on the distribution patterns of freshwater zooplankton, which can represent vital information for environmental managers.
Keywords: Cladocera; Copepoda; Dormant eggs; Ecotoxicology; Glyphosate; Rotifera